Hepatic arterial infusion is effective in patients with unresectable colorectal liver metastases refractory to standard systemic chemotherapy: A retrospective cohort study - Masatsugu Ishii; Osamu Itano; Hideki Iwamoto; Yuko Takami; Naomi Okada; Tetsuya Inoue; Satoshi Itano (PLoS ONE, 2025)
We identified an effective chemotherapy regimen in patients refractory to standard chemotherapy. We included patients with unresectable colorectal liver metastases who underwent hepatic artery infusion chemotherapy and systemic chemotherapy between January 2015 and December 2022. This study was a retrospective analysis conducted at a single center. The patients received either biweekly oxaliplatin and 5-fluorouracil through hepatic artery infusion chemotherapy as well as bevacizumab and leucovorin injected intravenously (HAIC-FOLFOX-B) or biweekly irinotecan and 5-fluorouracil by hepatic artery infusion chemotherapy and bevacizumab and leucovorin injected intravenously (HAIC-FOLFIRI-B). Of the 42 patients, 20 underwent HAIC-FOLFOX-B while 22 underwent HAIC-FOLFIRI-B treatment with response rates of 25% and 4.5%, respectively. The median overall survival and progression-free survival were 12.9 and 4.7 months and 17.4 and 7.7 months in patients undergoing HAIC-FOLFOX-B and HAIC-FOLFIRI-B, respectively. The overall incidence of grade 3/4 toxicity was 23.8%. However, no treatment-related deaths occurred. Functional catheter-associated problems occurred in 9.5% of the patients. Hepatic arterial occlusion occurred in three patients (7.1%); catheter-associated infection occurred in one (2.4%) patient. However, these occurrences were not life-threatening complications. HAIC-FOLFOX-B and HAIC-FOLFIRI-B might improve survival in patients with unresectable colorectal liver metastases and in those who underwent both systemic oxaliplatin-based and irinotecan-based chemotherapies and were refractory to them. HAIC FOLFOX-B and FOLFIRI-B regimens might be effective therapeutic options in patients with unresectable colorectal liver metastases refractory to standard systemic chemotherapy.